1999
DOI: 10.1095/biolreprod61.3.651
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Mainstream and Sidestream Cigarette Smoke Retards Embryo Transport and Slows Muscle Contraction in Oviducts of Hamsters (Mesocricetus auratus)1

Abstract: Prior experiments have shown that the functioning of hamster oviducts is impaired by in vitro exposure to cigarette smoke. To determine if cigarette smoke affects oviductal functioning in vivo, an inhalation experiment was done in which hamsters were exposed to doses of smoke similar to those received by human smokers. The effects of mainstream smoke (the bolus of smoke inhaled by active smokers) and sidestream smoke (the main component in environmental tobacco smoke) were compared. Transport of preimplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 26 publications
3
27
0
2
Order By: Relevance
“…Similar adverse effects may be associated with abuse of marijuana by women of reproductive age. This possibility is consistent with studies showing that women who smoke tobacco show an increased incidence of ectopic pregnancy (10), which correlates with the direct inhibitory effects of tobacco smoke and nicotine on oviductal transport of embryos in hamsters (11). Faah-null female mice are less fertile than wild-type females (9).…”
Section: Discussionsupporting
confidence: 90%
“…Similar adverse effects may be associated with abuse of marijuana by women of reproductive age. This possibility is consistent with studies showing that women who smoke tobacco show an increased incidence of ectopic pregnancy (10), which correlates with the direct inhibitory effects of tobacco smoke and nicotine on oviductal transport of embryos in hamsters (11). Faah-null female mice are less fertile than wild-type females (9).…”
Section: Discussionsupporting
confidence: 90%
“…Again sidestream smoke was more potent, and reduced contraction rates to 30% or less of the control rate for three harm reduction brands tested. These data show that chemicals in cigarette smoke inhibit oviductal contractions, in agreement with in vivo data (DiCarlantonio and Talbot, 1999), and help explain why embryo transport is retarded in females inhaling smoke. If similar inhibition of oviductal contraction occurs in human smokers, the effects could again lead to ectopic implantation in the oviduct or infertility; both problems seen in women smokers.…”
Section: Infundibularsupporting
confidence: 86%
“…Oviductal smooth muscle plays a role in movement of fertilized oocytes and preimplantation embryos through the oviduct (Croxatto, 2002). Since prior in vivo studies had shown inhibition of oviductal smooth muscle contraction is correlated with decreased movement of preimplantation embryos through the oviduct (DiCarlantonio and Talbot, 1999), the infundibular assay was further developed to measure contraction of infundibular muscle in vitro (Riveles et al, 2003). Strength of contraction was determined by measuring the distance the infundibulum moves during a contraction.…”
Section: Infundibularmentioning
confidence: 99%
“…Moving too quickly could result in expulsion of the embryo from the female tract prior to implantation, while retarded movement may result in implantation in an ectopic site. Animal studies have shown that inhalation of either MS or SS smoke retards movement of hamster preimplantation embryos through the oviduct (DiCarlantonio & Talbot, 1999). The doses that were effective in this study are similar to those found in human smokers based on measured values of cotinine in the serum of exposed hamsters.…”
Section: Animal Studies On Embryo Movement Though the Oviductsupporting
confidence: 74%